Investigating Anxiety Levels and Factor Between Gender in English Language Learning Among Diploma in English Students - Nur Atiqah Lewi; Siti Shuhaida Shukor; Arif Hakimi Zulazli; Yoshini K Sagaratis; Salbiah Hassan (Journal of Translation, Linguistics and Literature, 2025)
This study investigates anxiety levels among male and female students enrolled in a Diploma in English program at the tertiary level, focusing on three key factors which are communication apprehension, fear of negative evaluation, and test anxiety. The study employs both qualitative and quantitative methods, collecting data through questionnaires and interviews to provide a comprehensive understanding of the topic. The findings reveal that both genders experience anxiety to a similar extent. Male and female students experience anxiety from all three factors. Interview data further clarify similarities and differences in the aspects of these factors that cause anxiety. Implications for educators include the necessity of creating supportive, non-judgmental learning environments and implementing targeted interventions, such as additional grammar support for male students and stress management activities for female students. Future research should consider larger, more diverse samples and explore the impact of different teaching methods and technological tools on reducing language learning anxiety. This study contributes to the field by highlighting the importance of addressing anxiety to enhance ESL learners' academic success and overall well-being.